Complement activation and cellular inflammation in Fabry disease patients despite enzyme replacement therapy - Laffer, Björn; Lenders, Malte; Ehlers-Jeske, Elvira; Heidenreich, Karin; Brand, Eva; Köhl, Jörg (Frontiers in Immunology, 2024)
Defective α-galactosidase A (AGAL/GLA) due to missense or nonsense mutations in the GLA gene results in accumulation of the glycosphingolipids globotriaosylceramide (Gb3) and its deacylated derivate globotriaosylsphingosine (lyso-Gb3) in cells and body fluids. The aberrant glycosphingolipid metabolism leads to a progressive lysosomal storage disorder, i. e. Fabry disease (FD), characterized by chronic inflammation leading to multiorgan damage. Enzyme replacement therapy (ERT) with agalsidase-alfa or -beta is one of the main treatment options facilitating cellular Gb3 clearance. Proteome studies have shown changes in complement proteins during ERT. However, the direct activation of the complement system during FD has not been explored. Here, we demonstrate strong activation of the complement system in 17 classical male FD patients with either missense or nonsense mutations before and after ERT as evidenced by high C3a and C5a serum levels. In contrast to the strong reduction of lyso-Gb3 under ERT, C3a and C5a markedly increased in FD patients with nonsense mutations, most of whom developed anti-drug antibodies (ADA), whereas FD patients with missense mutations, which were ADA-negative, showed heterogenous C3a and C5a serum levels under treatment. In addition to the complement activation, we found increased IL-6, IL-10 and TGF-ß1 serum levels in FD patients. This increase was most prominent in patients with missense mutations under ERT, most of whom developed mild nephropathy with decreased estimated glomerular filtration rate. Together, our findings demonstrate strong complement activation in FD independent of ERT therapy, especially in males with nonsense mutations and the development of ADAs. In addition, our data suggest kidney cell-associated production of cytokines, which have a strong potential to drive renal damage. Thus, chronic inflammation as a driver of organ damage in FD seems to proceed despite ERT and may prove useful as a target to cope with progressive organ damage.